Motivation as a psychological factor of creativity - ALMONAITIENĖ, J. (Psichologija, 1997)
The article deals with the questions of creativity factors. Certain thinking abilities were considered for a while to be the main determinants of creativity, but the data of empirical research accumulated eventually contradicted this traditional standpoint. On the basis of the results of numerous investigations, the possibility was raised that a person's motivation (in the broad sense: motives, values, interests, etc.) may be an important determinant of creativity. This question was examined in the research presented in the article. The students who had exceptional achievements in, various real-life activities which demand creativity participated in the study and the original method of qualitative nature was used. It allowed for the inquiry of some new details of the content of such a creativity factor. The results showed that there were differences in more creative and less creative students' future plans, their attitudes towards their future careers, and the learning of various subjects. It appeared that intrinsic learning motives predominated among more creative students and extrinsic motives among less creative students.
Keywords: motivation; creativity; factors of creativty